Strategi Pengelolaan Lembaga Pendidikan Islam - Ryuzen, Ryuzen (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2017)
As a national education subsystem, Islamic education should contribute to building and improving the quality of Indonesian people by creating the best generation (khairunnas / goden generation), which is a generation that excels in science and technology and is able to practice it in daily life. To achieve this goal, Islamic education must be managed optimally through the Islamic Education Institution (LPI). Management of Islamic education institutions whose numbers and shapes are very large certainly requires its own strategy to achieve productivity and quality output. Various concepts and thoughts related to management strategies are urgently needed so that Islamic Education Institutions are no longer regarded as second-class educational institutions that have not been able to fulfill the people's beliefs and needs for quality education. In this paper two management strategies are offered, namely general strategies and specific strategies. In general, strategies are offered based on the Sirozi concept which includes substantive, bottom-up, deregulatory, and cooperative strategies. While specifically applying the management functions of Islamic Education (planning, organizing, implementing / directing and supervising) comprehensively and consistently is considered a smart and futuristic strategic step.